2020
DOI: 10.1002/anie.201914120
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Imaging Quantifies Drug Release from Nanocarriers via Redox Chemistry of Dye‐Labeled Cargo

Abstract: We report a new approach to monitor drug release from nanocarriers via a paclitaxel–methylene blue conjugate (PTX‐MB) with redox activity. This construct is in a photoacoustically silent reduced state inside poly(lactic‐co‐glycolic acid) (PLGA) nanoparticles (PTX‐MB@PLGA NPs). During release, PTX‐MB is spontaneously oxidized to produce a concentration‐dependent photoacoustic signal. An in vitro drug‐release study showed an initial burst release (25 %) between 0–24 h and a sustained release between 24–120 h wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…The reduction of methylene blue is a reversible and environment-dependent process, especially in oxygen-rich aqueous environments [40,41], which this system was. However, in semiconductor sensitized systems, the reduction of MB to its leuco form (LMB) is irreversible [42].…”
Section: The Effect Of the Amount Of The Photocatalystsmentioning
confidence: 90%
“…The reduction of methylene blue is a reversible and environment-dependent process, especially in oxygen-rich aqueous environments [40,41], which this system was. However, in semiconductor sensitized systems, the reduction of MB to its leuco form (LMB) is irreversible [42].…”
Section: The Effect Of the Amount Of The Photocatalystsmentioning
confidence: 90%
“…Wang et al had demonstrated a 492-folds increase in PA signal with MB encapsulated in sodium dodecyl sulfate (SDS) micelles [ 61 ]. Recently, Jeevarathinam et al utilized the redox chemistry of MB to photoacoustically quantify drug release from nanocarriers [ 62 ]. Paclitaxel conjugated to a chemically reduced form, leuco form methylene blue (LMB), which was encapsulated in a poly(lactic-co-glycolic acid) NP.…”
Section: Exogenous Contrast Agentsmentioning
confidence: 99%
“…Upon the release of paclitaxel, the PA silent LMB will be spontaneously oxidized into PA active MB. By monitoring the increase in PA signals generated by the MB, the amount of paclitaxel release can be quantified [ 62 ]. Nonetheless, most of these MPACs, like cyanine dyes, are susceptible to photoisomerization, photobleaching ( Figure 8 ), and solvatochromism.…”
Section: Exogenous Contrast Agentsmentioning
confidence: 99%
“…Future investigations may explore the potential benefit or harm of using isoniazid in the chemical composition of the present MNP formulation in vitro and in vivo. Furthermore, our research group will consider conducting studies to explore more directions related to the use of MNPs, such as the role of MNPs as acoustic imaging tools [51].…”
Section: In Vivo Oral Pharmacokinetic Studiesmentioning
confidence: 99%